Political candidates' attitudes towards group representation. Issue 3 (3rd July 2018) - Coffé, Hilde; Reiser, Marion
ABSTRACT: Our study examines the extent to which parliamentary candidates believe that membership of a certain social group allows Members of Parliament (MPs) to more effectively represent that group. Using the 2009 German Candidate Survey, we look at four social groups: women, immigrants, religious people and East Germans. The descriptive results indicate that support for group representation is highest for women and lowest for East Germans. The explanatory analyses reveal that women are more likely than men to believe that women are better at representing the interests of women. The same holds for immigrants, religious people, and East Germans. Candidates' belief that MPs from a certain social group are better at representing that group tends to be limited to their own social group. Our results thus indicate that the belief that one should belong to a social group in order to effectively represent the interests of that group is mainly based on identity, rather than an overall belief in the link between descriptive and substantive representation. They also show that attitudes towards representation change significantly as a result of parliamentary socialisation, with candidates with parliamentary experience being significantly less likely to support the idea of group representation compared with those without such experience.